MOTIVATION AND SATISFACTION TOWARDS EMPLOYEES’ LOYALTY TO ACHIEVE COMPANY’S ADVANTAGE - Sari, Evi Thelia (FEB Universitas Sam Ratulangi Manado, 2017)
The study aims to examine if employees’ motivation and satisfaction mediated by loyalty can result in company’s advantage. Using 100 young staffs and supervisors in either local or foreign companies in Surabaya, Indonesia as respondents and being tested using regression and path analysis. The simple regressions analysis in the study found that employee’s loyalty is not significant to influence company’s advantage and employee’s satisfaction is not significant to influence employee’s loyalty as well. Employee’s motivation significantly influences loyalty and company’s advantage. Employee’s satisfaction has significant influence to company’s advantage. Multiple regression tests shows that employee’s motivation has positive influence but employee’s satisfaction has negative influence to employee’s loyalty. Both employee’s motivation and employee’s satisfaction have positive influence to company’s advantage. Path analysis has the results that employee’s loyalty is not moderating variables between Employee’s motivation, employee’s satisfaction and company’s advantage.Keywords: motivation, satisfaction, loyalty, company’s advantage Indomaret and Alfamart are the example of a retail business in Indonesia, which is the market leader in their field. Both companies are mini network that provides basic needs and daily necessities. But the problems faced Indomaret and Alfamart are the position of those who are always nearby.These problems is not a barrier for both. This is caused by them are in the same market share, selling products that uniform and is in the center crowds. The purpose of this study was to determine differences in the level of service to consumers and alfamart Indomaret Karombasan.Keywords :motivation, satisfaction, loyalty, company’s advantage